ACTonDiabetes—a guided psychological internet intervention based on Acceptance and Commitment Therapy (ACT) for adults living with type 1 or 2 diabetes: results of a randomised controlled feasibility trial. Issue 7 (9th July 2021) - Bendig, Eileen; Bauereiss, Natalie; Schmitt, Andreas; Albus, Patrick; Baumeister, Harald
Abstract : Objectives: This two-group randomised controlled trial evaluates the feasibility of an Acceptance and Commitment Therapy (ACT)-based internet intervention for diabetes distress in people with diabetes type 1 or type 2. Participants were assigned to a guided self-help intervention (EG) or waitlist control group (CG). Setting: Recruitment took place following an open recruitment strategy including different diabetes centres, self-help groups and social media platforms. Participants: Eligibility criteria comprised being 18 years of age or older, self-reported diagnosis of type 1 or type 2 diabetes, internet access, sufficient German language skills and written informed consent. Intervention: ACTonDiabetes is an internet-based and mobile-based intervention and comprises an introduction and seven modules (one module per week, processing time about 45–60 min). Intervention contents are based on ACT. Primary and secondary outcome measures: Participants were assessed before and 8 weeks after randomisation. Primary outcome was feasibility (trial recruitment, acceptability). Potential group differences in diabetes distress and other outcomes at follow-up were analysed using linear regression models with baseline values as predictors. All analyses were based on an intention-to-treat principle, potential negative effects were analysed on per-protocol basis. Results: From October 2017 to April 2018, N=42 people with diabetes consented and were randomised (EG n=21, CG n=21). Forty-three per cent of the EG completed all treatment modules within 8 weeks. Across modules, formative user feedback revealed that contents could be optimised regarding comprehensibility (34%), individualisation (20%) and text amount (21%). Overall, 57% of participants dropped out prior to full treatment completion. There were reductions of diabetes distress in the EG (d=0.65, p=0.042). Conclusions: Modifications of the intervention content according to the user feedback will be performed to further improve acceptability. Mechanisms to foster intervention adherence should be considered for lowering the attrition rate. ACTonDiabetes is feasible for the implementation in a confirmatory trial. Trial registration number: WHO International Clinical Trials Registry Platform via the German Clinical Trials Register (DRKS) (DRKS00013193).